How are inflation targets set? - Roman Horváth; Jakub Matějů (Charles University in Prague, Institute of Economic Studies (IES), 2011)
This paper aims to contribute to a better understanding on how inflation targets are set. For this reason, we first gather evidence from official central bank and government publications and from a questionnaire sent to central banks on how inflation targets are set; we then estimate the determinants of the level of inflation target in 19 inflation targeting countries using unbalanced panel interval regressions (to deal with the issue that targets are typically set as a range rather than as a point). Inflation targets are found to reflect macroeconomic fundamentals. Higher level as well as higher variability of inflation are associated with higher target. The setting of the inflation target is also found to have an important international dimension, as higher world inflation is positively correlated with inflation targets. Rapidly growing countries exhibit higher inflation targets. Our results also suggest that the larger width of inflation target is set in a more volatile macroeconomic environment. We find that central bank credibility is negatively associated with the level of inflation target, suggesting that less credible central banks are likely to recognize the risks related to anchoring inflation expectations at low levels. On the other hand, government party orientation does not matter even in less independent central banks.
Keywords: E31; E42; E52; E58; 330; inflation targeting; central bank; inflation; credibility; independence; Inflationssteuerung; Zentralbank; Öffentlichkeitsarbeit; Glaubwürdigkeit; Zentralbankunabhängigkeit; Welt